Mapping of Dissaster-Prone Area for Residential Area Development: Evaluation in Barabai City, Hulu Sungai Tengah District, South Kalimantan - Rosalina Kumalawati (Center for Journal Management and Publication, 2016)
Flood disaster has some influences towards residential area. The effect of flood towards residential area needs to be investigated to determine the correct allocation of residential development space for the people who live in a flood-prone area. This research aims to develop a map of flood-prone areas for the sake of residential development evaluation in Baraba district, Hulu Sungai Tengah Regency, South Borneo.The purposive sampling technique was used to select the research area. The unit analysis is some districts and included in the flood-prone areas. To determine the sample based on flood-prone level, the stratified sampling was used.The result of the research shows that most of the investigated areas prone to flood. A secure location for resident should utilize the land in accordance with the criteria of safe and appropriate settlement layout. The low-prone and safe areas can be used for the space allocation of residential areas development in order to be safer from flooding.